Nurse-led early evaluation following corticosteroid prescription in patients with inflammatory bowel disease. (2nd December 2021) - Harvey, Philip R; Slater, Jayne; Algieder, Akram; Jones, Judith; Bates, Beth; De Silva, Shanika
Abstract : Background: The Toronto consensus for management of ulcerative colitis (UC) recommends early evaluation of UC patients 2 weeks after initiation on corticosteroids. A system for early evaluation of inflammatory bowel disease patients was established by specialist nurses in a secondary care centre. Aim: To compare outcomes following early evaluation to the previous service. Methods: All patients undergoing early evaluation over a 1-year period were prospectively audited and compared to a retrospective cohort of patients receiving prednisolone in the preceding year. Findings: Of 140 patients included, 76 (54.3%) underwent early evaluation. All patients in the early evaluation group received drug education and details of the nurse helpline (17.1% of patients did not already have this). Of patients, 81.6% were prescribed Adcal, and 83.9% were on 5-aminosalicylates. Fewer admissions were observed within 6 months following early evaluation (8.6% vs. 23.4%, p=0.013). Conclusion: Multiple benefits of early evaluation were observed, including a potential reduction in hospital admissions.